Management Skills of Administrators in the 21st Century Affecting Teacher’s Functional Competency in Opportunity Expansion Schools in Bangkok Metropolitan Administration, East Bangkok Zone - Sirion, Anongnard; Srimarut, Benjawan; Pranpa, Meanmas (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were 1) to study management skills of administrators in the 21st century, 2) to study teacher’s functional competency, 3) to study management skills of administrators in the 21st century affecting teacher’s functional competency, and 4) to propose the guidelines for improving management skills of administrators in the 21st century affecting teacher’s functional competency opportunity expansion schools in Bangkok metropolitan administration, East Bangkok Zone. The 269 samples were government teachers. The research instrument was a questionnaire with reliability of .99 and interview form. The descriptive statistics for data analysis were percentage, means, standard deviations (SD), and Stepwise Multiple Regression. The results showed that 1) the management skills of administrators in the 21st century in overall were at a high level, 2) the teacher’s functional competency in overall were at a high level, 3) the management skills of administrators in the 21st century affecting teacher’s functional competency opportunity expansion schools in Bangkok metropolitan administration, East Bangkok Zone were problem solving skills and technology skills at .01 level of statistically significance, and 4) the guidelines for improving management skills of administrators in the 21st century affecting teacher’s functional competency were found that the administrators should be skilled and use modern technology tools; manage work in a timely manner; know how to learn from real practice; be a learner; can give advice on how to work effectively. Also they have techniques, methods and operational processes to achieve the goals with a focus on curriculum administration and learning management. The curriculum has been revised to keep up with changes in technology.